Exploiting the co-reliance of tumours upon transport of amino acids and lactate: Gln and Tyr conjugates of MCT1 inhibitors12. Issue 5 (1st March 2016) - Nair, Reji N.; Mishra, Jitendra K.; Li, Fangzheng; Tortosa, Mariola; Yang, Chunying; Doherty, Joanne R.; Cameron, Michael; Cleveland, John L.; Roush, William R.; Bannister, Thomas D.
Abstract : Gln and Tyr conjugates of MCT inhibitors were designed and shown to be highly cytotoxic to a human cancer cell line expressing the transporters Asct2, LAT1, and MCT1/2. Abstract : Glutamine and tyrosine-based amino acid conjugates of monocarboxylate transporter types 1 and 2 inhibitors (MCT1/2) were designed, synthesized and evaluated for their potency in blocking the proliferation of a human B lymphoma cell line that expresses the transporters Asct2, LAT1 and MCT1. Appropriate placement of an amino acid transporter recognition element was shown to augment anti-tumour efficacy vs. Raji cells. Amino acid conjugation also improves the pharmacodynamic properties of experimental MCT1/2 inhibitors.